Navigating Generative AI: Opportunities, Limitations, and Ethical Considerations in Massage Therapy and Beyond - Baskwill, Amanda (International Journal of Therapeutic Massage & Bodywork, 2023)
Generative artificial intelligence (AI) has become a hot topic, particularly ChatGPT's quick adoption and popularity, prompting discussions about its disruptive potential in health care, education, and creative sectors. The author, an early adopter, shares personal insights on leveraging generative AI for creative tasks and communication challenges, while also exploring its role as a tool rather than an author. Opportuni-ties and limitations of integrating generative AI in the massage therapy field are explored, reflecting on the profession's reluctance to embrace technology and the potential efficiency gains. While acknowledging generative AI's creative promise, the importance of ethical and regulated utilization, highlighting data biases and limitations, is underscored. Overall, a balanced and responsible approach to incorporating generative AI into various domains is recommended.